Electropolymerisation and properties of conducting polymers derived from aminobenzenesulphonic acids and from mixtures with aniline - Thiemann, Carolin (2001)
The electrochemical polymerisation of 2- and 4-aminobenzenesulphonic acids (orthanilic acid and sulphanilic acid) in sulphuric acid solution and co-polymerisation of mixtures of aniline and acid monomers, have been systematically investigated. The polymers formed have been characterised voltammetrically. Further evidence concerning the polymer structure and chemical composition has been obtained by IR spectroscopy and scanning electron microscopy (SEM).